Peran Global Fund dalam Konteks Keamanan Manusia di Sulawesi Selatan: Studi Kasus Penyakit Tuberkulosis - Dhani Hady Pratama; Farahdiba Rachma Bachtiar (Department of International Relations, Hasanuddin University, 2022)
Security is not only about the freedom of the state from military threats, but also free from non-traditional threats such as health. In the case of TB, for example, which may not as popular as the Covid-19 virus, there are 1.2 million people in the world who die every year. For this reason, as a global agenda in the Sustainable Development Goals (SDGs), TB disease such as HIV/AIDS and Malaria must be addressed together. To that end, the United Nations encourages the establishment of the Global Fund (GF). GF is an international funding agency that works in the health sector. In Indonesia, the GF has been present since 2003 both with the Indonesian government and various community organizations, including in the context of South Sulawesi, namely the TB Care Community Foundation (YAMALI). For this reason, this study discusses the role of the GF in the context of human security in South Sulawesi with case studies of Tuberculosis (TB). The research method used was case study research by extracting data from documents or literature studies and field study by conducting interviews. The author finds that the role of GF through YAMALI is significant and widespread in ending TB in Indonesia. This is reflected in the various programs carried out, both directly and fully funded by GF and which are self-managed by YAMALI. This shows that studies and phenomena of international relations are no longer able to only be seen as big narratives or global agendas in the SDGs which are sufficiently managed by state elites or power holders who often dwell on high-level political issues. However, the issue of cross-border global development that is now included in the SDGs should be oriented towards People (Humans), Planet (Earth), Prosperity (Prosperity), Peace (Peace), and Partnership (Partnership). Keamanan tidak hanya seputar bebasnya negara dari ancaman militer saja, namun juga oleh ancaman non-tradisional seperti kesehatan. Dalam kasus TB misalnya yang meskipun tidak sepopuler virus Covid-19, terdapat1,2 juta orang di dunia yang meninggal setiap tahunnya. Untuk itu, sebagai agenda global dalam Sustainable Development Goals (SDGs) penyakit TB sebagaimana HIV/AIDS dan Malaria harus diatasi bersama. Untuk itu, PBB mendorong pembentukan lembaga Global Fund. (GF). GF merupakan lembaga pendanaan internasional yang bekerja di bidang kesehatan. Di Indonesia, GF telah hadir sejak 2003 baik dengan pemerintah Indonesia maupun berbagai organisasi masyarakat termasuk dalam konteks Sulawesi Selatan yakni Yayasan masyarakat Peduli TB (YAMALI). Untuk itu penelitian ini membahas mengenai peran Global Fund dalam konteks keamanan manusia di Sulsel dengan studi kasus Penyakit Tuberkulosis (TB). Adapun metode penelitian yang digunakan adalah penelitian studi kasus dengan menggali data dari dokumen atau studi pustaka dan studi lapangan dengan melakukan wawancara. Penulis menemukan bahwa peran GF melalui YAMALI signifikan dan meluas dalam mengkahiri penyakit menular TB di Indonesia. Hal ini tercermin dari berbagai program yang dijalankan baik yang secara langsung dan penuh didanai oleh GF maupun yang dikelola sendiri oleh YAMALI. Hal ini menunjukkan bahwa kajian dan fenomena hubungan internasional tidak lagi hanya mampu dipandang sebagai narasi besar atau agenda global dalam SDGs yang cukup dikelola oleh elit negara atau pemegang kekuasaan yang sering berkutat pada persoalan politik tingkat tinggi. Namun, seharusnya isu pembangunan global lintas batas negara yang kini tercakup dalam SDGs harus berorientasi pada People (Manusia), Planet (Bumi), Prosperity (Kemakmuran), Peace (Perdamaian), dan Partnership (Kemitraan).